STRUKTUR KOMUNITAS TERIPANG (HOLOTHUROIDEA) DI PERAIRAN TANJUNG MERAH, SELAT LEMBEH SULAWESI UTARA - Eddy Yusron; Susetiono Susetiono (Universitas Gadjah Mada, 2006)
During January 2005 the holothurian community inhabiting littoral areas was assessed at five station on four ecological indices: density, species richness, diversity and evenness. It was revealed that the holothurian community consisted of 8 species in which three among them occurred in all locations at higher densities: Holothuria edulis, H. scabra and H. atra. Small variations of the ecological indices found in all location might indicated that the community characteristics among locations were relatively similar.